Comparative Study of Serum Vitamin D and Calcium in Patients With and Without Temporomandibular Joint Disorder: An Institutional Study - Panthee, Anuja; Panthee, Asmita; Khapung, Anju (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Calcium homeostasis, an essential component of musculoskeletal system requires Vitamin D as its integral element. Many studies have demonstrated the inconclusive association between serum calcium and some factors involved in calcium metabolism such as vitamin D. Objectives The aim of this present study is to evaluate the serum level of vitamin D and calcium in patient with and without Temporo-mandibular Joint disorder (TMDs) and to determine the association of same with age and gender. Methods: An observational, comparative, quantitative, cross sectional study was done over a period of 6 months. Serum analysis of vitamin D and calcium was done for patients, with and without TMDs, visiting Oral and Maxillofacial Surgery (OMFS) Out Patient Department (OPD) from May to october 2022. Data analysis was done using chi square and independent t test. Results A total of 200 study participants were included in the study of which 100 (50.00%) had TMDs and 100 (50.00%) did not have those problems. The difference in Vitamin D level were found statistically significant in those with and without TMJ problems. Conclusion There was statistically significant association between serum Vitamin D and TMDs whereas there was no association between serum calcium and TMDs.